In-situ biofouling mitigation using ultrasonication in membrane bioreactor - Mohamad Idris, Aida Isma (2016)
This thesis investigates the biofouling mitigation in a membrane bioreactor (MBR) using ultrasonication method. Membrane fouling is recognized as a major drawback for the application of wastewater treatment and has remained a critical limiting factor for wide spread application of the technology. Membrane biofouling is characterized as soluble microbial products and extracellular polymeric substances in the form of protein and polysaccharides concentration. Fouling was observed by the increment of the trans-membrane pressure (TMP) and assumed to occur first by pore blockage followed by cake formation over the blocked pores.Characterization results showed that the concentration of the soluble microbial products (SMP) ranged from 10.76 to 30.72 and 5.97 to 17.05 mg/L for polysaccharides and protein, respectively, and the extracellular polymeric substances (EPS) ranged from 9.87 to 38.70 and 10.56 to 28.85 mg/L for polysaccharides and protein, respectively, at SRT of 30 days. The SMP fraction is considered the main contributor to membrane fouling via adsorption of macromolecules and pore clogging. The evaluation on the performance of membrane bioreactors has been carried out by changing the operating parameters of the system with solids retention time and hydraulic retention time of 30, 15, and 4 days and 12, 8 and 4 hours, respectively. The best removal efficiencies recorded were at SRT 30 days and HRT 12 hours. Removals of COD, BOD, NH3-N and PO43- achieved at 95%, 93%, 98% and 81%, respectively. Results demonstrated that the COD removal efficiency decrease from 95.31% (at HRT 12) to 92.86% (at HRT 8) and further decreased to 92.79% (at HRT 4). The NH3-N removal efficiency decreased from 97.60% (at HRT 12) to 91.03% (at HRT 8) and remains at 91.25% (at HRT 4). Fouling morphology proves that there were two types of fouling observed which are biofilm and the cake layer formation.Mitigating membrane biofouling using an in-situ ultrasonication method was carried out at a cleaning frequency of 28 kHz for 10 min contact time with and without chemicals. The best recoveries achieved were 57 and 67% with and without cleaning agents. It should be noted that the best flux recoveries achieved was by using 1.0 M of NaOH and NaOCl, with flux recoveries of 55 and 50%, respectively.The economic viability of the integrated system showed that it is able to treat effluent with the cost of RM 4.04 per cubic meter with longer operation time, space saving due to in-situ cleaning and the selected sequence could be prolong the treatment process up to three cycle of the normal membrane filtration system. Hence, it can be concluded that this integrated system is cost effective, environmental friendly, space saving and could offer an alternative method in mitigating membrane fouling in a membrane bioreactor.